A Case of Acute Hypertriglyceridemia-Induced Pancreatitis in Pregnancy and Its Clinical Implications - Corley Rachelle Price; Anthony Kendle; Mary Ashley Cain (Case Reports in Endocrinology)
Acute hypertriglyceridemia-induced pancreatitis (HTGP) is an uncommon occurrence during pregnancy. Prompt diagnosis and initiation of treatment are indicated to prevent adverse maternal and neonatal outcomes. We present the case of a pregnant female who was diagnosed with HTGP at 34 weeks gestation and subsequently developed diabetic ketoacidosis (DKA) and preeclampsia with severe features. We describe the pathophysiology of acute HTGP and its relation to the gravid state and review available treatment options though data remains limited. Our case emphasizes the potential sequelae of HTGP in pregnancy, the need for a multidisciplinary approach for optimal care, and the importance of early treatment in improving maternal and neonatal outcomes.